Effects of early childhood intervention on child development and early skill formation: Evidence from a randomized controlled trail - Malte Sandner (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2013)
This paper presents results from a randomized evaluation of a home visiting program for disadvantaged first-time mothers and their families implemented in Germany. 12 months after birth, the intervention increases infants' cognitive development by 0.18 SD. However, the effect fades out after 24 months. Gender analyses reveal that the intervention was more beneficial for girls. Furthermore, sensitivity analyses show that the estimated effects seem downward biased by additional treatment for the control families. Analyzing the infant skill formation process reveals self-productivity of skills but in different magnitude for boys and girls.
Keywords: J13; J12; I21; H52; 330; Early Childhood Intervention; Randomized Experiment